2020
DOI: 10.1093/ndt/gfz296
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil count and mortality risk in incident hemodialysis patients

Abstract: Background Eosinophils are traditionally known as moderators of allergic reactions; however, they have now emerged as one of the principal immune-regulating cells as well as predictors of vascular disease and mortality in the general population. Although eosinophilia has been demonstrated in hemodialysis (HD) patients, associations of eosinophil count (EOC) and its changes with mortality in HD patients are still unknown. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…EOC in men and women showed significant differences both before and after dialysis (190.0 vs. 130.0/μL, p < 0.001; 239.3 vs. 161.9/μL, p < 0.001, respectively) in our study. This is consistent with studies of eosinophils in a healthy population, predialysis CKD patients, and HD patients, all of which reported EOC was higher in men than in women [11,25,26]. These results indicate that gender itself contributes to the different domain value of EOC instead of the effect caused by PD therapy, suggesting gender should be considered when defining the "normal" values of EOC.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…EOC in men and women showed significant differences both before and after dialysis (190.0 vs. 130.0/μL, p < 0.001; 239.3 vs. 161.9/μL, p < 0.001, respectively) in our study. This is consistent with studies of eosinophils in a healthy population, predialysis CKD patients, and HD patients, all of which reported EOC was higher in men than in women [11,25,26]. These results indicate that gender itself contributes to the different domain value of EOC instead of the effect caused by PD therapy, suggesting gender should be considered when defining the "normal" values of EOC.…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, even though older age was a significant risk factor for technique failure in women (with each 1 year increase, HR: 1.021; 95% CI: 1.005–1.037; p = 0.009), the significant association of eosinophilia with technique failure was only observed in women aged <55 years but not in women aged ≥55 years. Similar results were reported for HD patients, which indicated that a higher EOC was more likely to be associated with mortality in younger patients [11]. Together, these data consolidate our hypothesis that estrogen has a role on the function of eosinophils and thus explains in part the differences observed between males and females with eosinophilia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, although currently, we have no direct explanation for the higher eosinophil counts seen in HD patients, this may also indicate substantial immune activation during the HD process. Interestingly, changes (both low or high) in eosinophil counts were previously associated with higher all-cause mortality in incident HD patients [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 and 4 events per 100 patient-months of follow-up, respectively) [20]. In a national cohort of 58 304 incident hemodialysis patients with and without diabetes from a large dialysis organization (LDO), 17 and 7% of patients, respectively, were found to have hypoglycemia as ascertained by monthly predialysis glucose levels [21].…”
Section: Hypoglycemia In Chronic Kidney Diseasementioning
confidence: 99%